2010
DOI: 10.1152/jn.00661.2009
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Enhances Procedural Consolidation

Abstract: The primary motor cortex (M1) area recruitment enlarges while learning a finger tapping sequence. Also M1 excitability increases during procedural consolidation. Our aim was to investigate whether increasing M1 excitability by anodal transcranial DC stimulation (AtDCS) when procedural consolidation occurs was able to induce an early consolidation improvement. Forty-seven right-handed healthy participants were trained in a nine-element serial finger tapping task (SFTT) executed with the left hand. Random series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
101
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 44 publications
12
101
5
Order By: Relevance
“…The effects of anodal tDCS on online sequence learning have been a particular area of interest (Amadi, Allman, Johansen-Berg, & Stagg, 2015;Ambrus et al, 2016;Cuypers et al, 2013;Kang & Paik, 2011;Kantak, Mummidisetty, & Stinear, 2012;Karok & Witney, 2013; M. F. Kuo et al, 2008;Nitsche et al, 2010;Nitsche et al, 2003;Reis et al, 2015;Reis et al, 2009;Stagg, Jayaram, et al, 2011;Tecchio et al, 2010;Vines, Cerruti, & Schlaug, 2008;Wade & Hammond, 2015). In an initial study, Nitsche and colleagues (2003) showed that anodal tDCS applied over M1 concurrently with training improved online implicit learning of a motor sequence, while stimulation applied to PMd, DMPFC and DLPFC did not .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
“…The effects of anodal tDCS on online sequence learning have been a particular area of interest (Amadi, Allman, Johansen-Berg, & Stagg, 2015;Ambrus et al, 2016;Cuypers et al, 2013;Kang & Paik, 2011;Kantak, Mummidisetty, & Stinear, 2012;Karok & Witney, 2013; M. F. Kuo et al, 2008;Nitsche et al, 2010;Nitsche et al, 2003;Reis et al, 2015;Reis et al, 2009;Stagg, Jayaram, et al, 2011;Tecchio et al, 2010;Vines, Cerruti, & Schlaug, 2008;Wade & Hammond, 2015). In an initial study, Nitsche and colleagues (2003) showed that anodal tDCS applied over M1 concurrently with training improved online implicit learning of a motor sequence, while stimulation applied to PMd, DMPFC and DLPFC did not .…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
“…As Horvath and colleagues note , even seemingly innocuous activities performed during stimulation, such as reading, talking or texting, may interfere with tDCS effects. There is clearly a need for further research to determine whether applying tDCS prior to, during, or even after (Tecchio et al, 2010) task practice leads to the greatest task performance benefits.…”
Section: Meta-analytic Findingsmentioning
confidence: 99%
“…Therefore, it is conceivable that tDCS, with its putative effects on cortical excitability (which may operate via glial-neuron interactions rather than neural stimulation directly), could enhance neural replay and therefore enhance consolidation. Though a direct demonstration is lacking, several studies have applied tDCS during waking rest at time periods when replay is thought to occur (Javadi and Cheng 2013;Sandrini et al 2014;Tecchio et al 2010) and subsequently demonstrated greater consolidation. Similarly, the application of slow-oscillating tDCS during slow-wave sleep has been shown to enhance declarative memory (reviewed in Barham et al 2016).…”
Section: Neurobiology Of Consolidation and Tdcsmentioning
confidence: 99%
“…For example, stimulation immediately after, but not during, training of a finger-tapping task enhanced subsequent performance 30 min later, presumably by facilitating early consolidation of procedural memory (Tecchio et al 2010). Similarly, reactivation of a previously learned word list hours or a day later led to better retention if stimulation was administered directly during this reactivation/reconsolidation period (Javadi and Cheng 2013;Sandrini et al 2014).…”
Section: Timing Of Stimulationmentioning
confidence: 99%